Communication Barriers in Human Resource Management and Education Quality in Mandailing Natal - Darwin Nasution; Alfred Kieser (Feedback International Journal of Communication, 2024)
Communication plays a pivotal role in effective human resource management (HRM), influencing organizational success, particularly in education. In Mandailing Natal, communication barriers significantly impact HR performance and educational quality. This study uses qualitative analysis, reviewing literature, surveys, and interviews with HR professionals and educators in Mandailing Natal to identify common communication challenges and their effects on educational outcomes. The findings reveal key barriers such as unclear communication channels, lack of structured feedback, and inadequate training. These challenges often lead to decreased motivation and discipline among educators, directly impacting the quality of education. Addressing these barriers requires establishing clear communication frameworks, aligning HR competencies with organizational goals, and improving training programs. Additionally, fostering an open communication culture within educational institutions is crucial. To improve education quality in Mandailing Natal, it is essential to overcome communication barriers in HR management through better resource allocation, structured communication strategies, and enhanced training. Effective communication is key to achieving higher staff performance and educational outcomes.